Students’ Perception of Debate Strategy as a Speaking Activity in EFL Classrooms - Fatimatuz Zahro; Anita Fatimatul L; Widya Oktarini (Journal of Educational Sciences, 2026)
Speaking skill is one of the most important aspects of English language learning, yet many students face difficulties in expressing ideas confidently due to limited speaking opportunities in teacher-centered classrooms. This study aimed to investigate tenth-grade students’ perceptions of the use of debate strategy in improving English speaking skills at SMA Muhammadiyah Rambipuji. The research employed a mixed-method approach involving 11 students (4 males and 7 females) from a total of 17 students in the class. Quantitative data were collected through a questionnaire using a Likert scale, while qualitative data were obtained through semi-structured interviews. The findings showed that 75% of the students perceived debate as an effective strategy for improving their speaking ability, particularly in terms of confidence, vocabulary mastery, fluency, and idea organization. Interview results further revealed that debate activities encouraged active participation and increased students’ motivation to speak English, although some students experienced anxiety during spontaneous argumentation. In conclusion, debate strategy is positively perceived by students and can serve as an effective alternative instructional strategy to enhance speaking skills and communicative competence in English language classrooms when implemented with appropriate guidance and preparation.